Form for reporting Iowa Christmas bird counts to Iowa Bird Life, Robert I. Cecil, January 3, 1987 - Cecil, Robert I.et al (1987)
Iowa Christmas bird counts of regular and uncommon species found in Keokuk contributed by Robert I. Cecil, January 3, 1987. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of winter 1986-1987. Epson - sheet feed